Advances in the approach to novel drug clinical development for breast cancer. (June 2014) - Ferrario, Cristiano; Batist, Gerald
<x xml:space="preserve">Abstract</x> Introduction: In the post-genomic era clinical development of new agents to treat breast cancer (BC) can be a real challenge. Different from chemotherapy agents, with a broad but not specific spectrum of activity, novel drugs are being developed as 'targeted' agents, potentially benefiting a subgroup of patients. In BC, different clinically identifiable subtypes are now separately addressed in specific clinical trials. Areas covered: In this review, the authors discuss the clinical development of targeted drugs that have become part of the current treatment of BC. They also highlight the challenges that in other cases determined the failure of promising compounds. Furthermore, the article reports on how combinations of targeted agents have emerged as valid strategies to overcome acquired resistance. It also provides discussion of how 'old' therapies can be retargeted to certain patient populations or 'reinvented' as safer and more effective with the creation of drug conjugates. They also discuss how novel clinical trial designs are emerging to accelerate the successful matching of targeted drugs to the right patient population. Expert opinion: It is important not to forget that the development of BC therapeutics is a 'moving target', as its biology evolves in time under the pressure of ongoing treatments. There are currently a finite number of resources available for the development of new therapeutics, which means that resources need to be carefully allocated. There is also a need to prioritize clinical trials that can reduce the number of patients who are candidates for expensive treatments.